An examination of labour discrimination in South Africa 2005-2008 : discussion and sensitivity analysis - Barnett, Luke (School of Economics, 2014)
Unemployment levels in South Africa are some of the highest in the world. Since the birth of democracy in 1994, the South African government has not only made employment a major focal point, but also the reduction in unemployment inequality. Using probit analysis, as well as non-linear decomposition techniques, this paper investigate the effects these policies have had on the labour market, in light of the recent economic recession experienced locally and abroad. Results indicate that racial labour discrimination still exists within the workplace, however whether this is due to differing endowments or pure discrimination is still a contentious issue.